The relation between coping style and posttraumatic growth among patients with breast cancer: A meta-analysis - Wan, Xiao; Huang, Haitao; Peng, Qianwen; Zhang, Yiming; Hao, Jiwei; Lu, Guangli; Chen, Chaoran (Frontiers in Psychology, 2022)
Posttraumatic growth (PTG) has been correlated with coping style among patients with breast cancer. However, to date, there is no consensus on the extent to which coping style is associated with PTG in patients with breast cancer. Therefore, we performed a meta-analysis to quantitatively synthesize previous findings. Based on the PRISMA method, this study employed a random effects model using the Stata software (version 16.0) to calculate the pooled correlation coefficient and examined a range of moderators: cancer stage, publication type, participants’ age, and coping style measurement tools. Relevant studies, published from inception to 9 March 2022, were identified through a systematic search in PubMed, Embase, Web of Science, PsycINFO, WANFANG DATA, Chinese National Knowledge Infrastructure (CNKI), and China Science and Technology Journal Database (VIP) databases. Finally, 20 studies involving 3,571 breast cancer patients were included in this investigation. The results showed a high positive relation between confrontation coping and PTG and a moderate positive relation between avoidance coping and PTG (confrontation: r = 0.456; avoidance: r = 0.291). Additionally, a moderate negative relation was identified between acceptance–resignation coping and PTG (r = –0.289). Publication type and coping style measurement tools moderated the relation between coping style and PTG among breast cancer patients. The findings indicated that breast cancer patients should either confront the disease or avoid coping with it according to their disease state, which would facilitate better growth. More studies, especially, large prospective studies, are warranted to verify our findings. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022319107], identifier [CRD42022319107].